Pentingnya Sarana Media Sosial Dalam Misi Gereja Di Situasi Pandemi Covid-19 - Christina Sianturi; Junjungan Simorangkir (Institut Agama kristen Negeri Tarutung, 2021)
Abstract: The emergence of the Corona virus towards the end of 2019, has caused an outbreak of disease globally, many countries are still grappling with this virus until this moment. The existence of the Corona virus which easily infects mankind has hampered human activities in various aspects, has a good impact on discomfort, jobs, development, the economy, and many more. Various preventive measures are encouraged by the government in cooperation with the regions to minimize its spread as much as possible, so that it does not affect other aspects. The church as an institution and an organism is also affected by it, ranging from online worship, to as much as possible to minimize face-to-face, and several other things. Not only that, It turns out that the spread of the Corona virus has an impact on the implementation of the mission of the church. The church, which has been carrying out various religious activities physically, is forced to use various digital media so that Christians can still get services; evangelism that could be done face to face, but in the midst of the COVID-19 pandemic situation, it is difficult for churches to do face to face. The church needs to respond quickly, appropriately and wisely to understand the application of social media as a means of evangelism. Given that basically any situation should not hinder the preaching of the gospel, including the COVID-19 pandemic. Here the church will take a relevant evangelistic role from the application of social media. The research method that the author uses to answer questions about the importance of social media facilities in carrying out the mission of the church during the COVID-19 pandemic is a descriptive qualitative research method. The aim is to describe how important the role of social media is in supporting the mission of the church during the COVID-19 pandemic. By building an evangelistic facility using social media, the news about Jesus Christ can be conveyed to many people at the same time, is not limited by age, is not limited by the dimensions of space and time, nor is it limited by national borders with all its bureaucracy. Keywords: Social Media; Mission Church; The COVID-19 pandemic Abstrak: Munculnya virus Corona menjelang akhir tahun 2019, telah menimbulkan wabah penyakit secara global, banyak negara-negara yang masih bergulat dengan virus ini hingga detik ini. Keberadaan virus Corona yang mudah sekali menjangkiti umat manusia telah menghambat aktivitas manusia dalam berbagai aspek, berimbas baik bagi ketidaknyamanan, pekerjaan, pembangunan, perekonomian, dan masih banyak lagi. Berbagai Tindakan pencegahan digalakkan oleh pemerintah bekerjasama dengan daerah untuk sedapat mungkin meminimalkan penyebarannya, sehingga tidak berimbas pada aspek lainnya. Gereja sebagai institusional dan organisme turut terkena dampak darinya, mulai dari peribadatan secara online, untuk sebisa mungkin meminimalkan tatap muka, serta beberapa hal lainnya. Tidak hanya itu ternyata penyebaran virus Corona berdampak pada pelaksanaan misi gereja. Gereja yang selama ini menjalankan berbagai kegiatan keagamaan secara fisik terpaksa menggunakan berbagai media digital agar umat Kristiani tetap bisa mendapatkan pelayanan; penginjilan yang tadinya dapat dilakukan secara face to face, tetapi ditengah situasi pandemi COVID-19 sulit bagi gereja untuk melakukan tatap muka. Gereja perlu menanggapi secara cepat, tepat dan bijaksana untuk memahami penerapan media sosial sebagai sarana penginjilan. Mengingat pada dasarnya keadaan apapun tidak boleh menghalangi pemberitaan Injil termasuk pandemi COVID-19. Metode penelitian yang penulis gunakan untuk menjawab pertanyaan mengenai pentingnya sarana media sosial dalam melakukan misi gereja di masa pandemi COVID-19, adalah metode penelitian kualitatif deskriptif. Tujuannya adalah untuk mendeskripsikan bagaimana pentingnya peranan sarana media sosial dalam mendukung misi gereja di masa pandemi COVID-19. Dengan membangun sebuah sarana penginjilan menggunakan media sosial maka berita tentang Yesus Kristus dapat disampaikan kepada banyak orang dalam waktu yang bersamaan, tidak dibatasi usia, tidak dibatasi oleh dimensi ruang dan waktu, juga tidak dibatasi oleh batas-batas negara dengan segala birokrasinya. Kata Kunci: Sosial Media; Misi Gereja; Pandemi COVID-19